1992
DOI: 10.1111/j.1432-1033.1992.tb16923.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in vitro of scallop muscle arginine kinase with filamentous actin

Abstract: Scallop muscle arginine kinase binds to F-actin from mollusc and rabbit muscle in vitro. One site of interaction appears to be located in residues 305 -325 of a C-terminal fragment (residues 285 -375) of actin. The binding is hindered in the presence of arginine, Mg2+-ADP and NO;, which form a dead-end complex with the enzyme. F-actin inhibits the enzyme activity non-competitively with respect to Mg2+-ATP. As a function of arginine concentration, the inhibition is of the mixed type, where K,,, is affected more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…The upregulated expression of AK on the 14th d.p.i of our current study suggests a possible additional energy supply favoring muscle regeneration. Overall, AK's role was depicted as the supply of additional adenosine tri phosphate (ATP) under exhausted and acidic environments (Ellington, ; Walter, Barton, & Sweeney, ), binding to actin with a reasonable affinity in the scallop muscle (S. R. Reddy, Houmeida, Benyamin, & Roustan, ), and the coupling of energy production and immune responses in shrimps (Arockiaraj et al, ; Yao, Ji, Kong, Wang, & Xiang, ). Although AK is clearly abundant in muscle and has a functional role in ATP regulation, the understanding of its relationship to muscle formation, especially in extreme conditions such as muscle regeneration or degeneration, muscle‐related diseases, and necrosis, is yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated expression of AK on the 14th d.p.i of our current study suggests a possible additional energy supply favoring muscle regeneration. Overall, AK's role was depicted as the supply of additional adenosine tri phosphate (ATP) under exhausted and acidic environments (Ellington, ; Walter, Barton, & Sweeney, ), binding to actin with a reasonable affinity in the scallop muscle (S. R. Reddy, Houmeida, Benyamin, & Roustan, ), and the coupling of energy production and immune responses in shrimps (Arockiaraj et al, ; Yao, Ji, Kong, Wang, & Xiang, ). Although AK is clearly abundant in muscle and has a functional role in ATP regulation, the understanding of its relationship to muscle formation, especially in extreme conditions such as muscle regeneration or degeneration, muscle‐related diseases, and necrosis, is yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…3). In this context it is noteworthy that scallop muscle arginine kinase AK1 binds to filamentous actin, leading to noncompetitive inhibition of the enzyme (33). Recently, the crystal structure of arginine kinase from the horseshoe crab (Limulus polyphemus) has been reported (34 Fig.…”
Section: Identification Of Arginine Kinase As P Interpunctella Allergenmentioning
confidence: 99%
“…It is understood that the reason for binding of AK to filamentous actins derived from shellfish is associated with the interaction of sequences of actin conserved during evolution (Newsholme et al 1978). Some AKs contain an a-actin like actin binding region (Pereira et al 2000), and it has been shown that AK from scallop muscle binds actin with reasonable affinity (Reddy et al 1992). Binding sites for the enzyme in the actin sequence were described by Lebart et al (1990) and Kabsch et al (1991).…”
Section: Discussionmentioning
confidence: 96%
“…function analogous to that of creatine kinase in vertebrates (Watts 1968). Abalone (Nordotis madaka), shrimp (Penaeus japonicus), crab (limulus polyphemus) and scallop (Pecten maximus) were found in the deduced amino-acid sequence of AK (Suzuki and Furukohri 1994;Turbeville et al 1991;Reddy et al 1992). Although AK is most widely distributed among invertebrates, considerable uncertainty exists as to inter-relationships of the various phosphagen kinase.…”
Section: Discussionmentioning
confidence: 97%